BIOÉTICA E NECROPOLÍTICA (Reflection and Critique Law Magazine, 2025)
This article consists of a discussion and analysis of the themes of biopower, necropolitics and separately and how they are interconnected in the current scenario of world governments. The concept of biopower will be analyzed through Michael Foucault's concept in conjunction with the analysis of the term necropolitics, from the perspective of thinker Achille Mbembe. The analysis of bioethics will be consolidated based on studies based on the same authors and also by the author and lawyer Henderson Furst. To introduce the scope of law, the term biolaw will be introduced, under Furst's analysis. In the analysis of the three themes, government oppression against socially vulnerable groups and the impacts of these oppressions on society will be referenced. Furthermore, the intersection between bioethics and necropolitics will be discussed and how concepts are lost under the banality of evil - a study carried out by German philosopher Hannah Arendt. The objective of the article is to disseminate knowledge on the topics so that the State is the target of demanding social improvements from the population, through the implementation of effective public policies and application of existing legislation. The methodology used in the research is qualitative, based on philosophical, sociological, legal and activist questions.